Faktor- faktor yang Berhubungan dengan Kepuasan Peserta ASKES Sosial dalam Pelayanan Dokter Keluarga PT. ASKES (Persero) - Alicia .; Yanwir Kamal (Jurnal Kesehatan Komunitas, 2013)
Figures Social Askes visits to health services Family Physicians PT. Health insurance (Persero) in Kuantan District Sengingi in 2010 decreased which begs the question and find the cause of the decline Askes visits to health care in the family doctor. The purpose of this study was to determine the factors associated with satisfaction in the Social Askes family doctor services in PT. Askses (Persero) in Kuantan District Sengingi. This research is quantitative analytic cross sectional design. Subjects in this study were 97 participants social Askes. Collecting data using questionnaires with the analyzed variables Administrative Services, Medical Services, and Infrastructure in Family Doctor. Statistical tests using Chi square test with p values significancy (p-value) <0.05. The results showed no relationship Administrative Services, Medical pelayana, and Infrastructures in the Family Physician satisfaction Askes Social PT. Health insurance (Persero) in Kuantan District Singingi. Doctors advised the family in order to maintain and improve the system of administrative services, medical services and infrastructure in order to improve the quality of care and satisfaction Askes social, family doctors can provide care that is promotive and preventive, PT. Health insurance (Persero) Regency Kuantan Sengingi more family doctors to promote the existence of the Social Askes